Associations between mesolimbic connectivity, and alcohol use from adolescence to adulthood - Angelica M. Morales; Scott A. Jones; Birgitta Carlson; Dakota Kliamovich; Joseph Dehoney; Brooke L. Simpson; Kalene A. Dominguez-Savage; Kristina O. Hernandez; Daniel A. Lopez; Fiona C. Baker; Duncan B. Clark; David B. Goldston; et al. (Developmental Cognitive Neuroscience)
Dopaminergic projections from the ventral tegmental area (VTA) to limbic regions play a key role in the initiation and maintenance of substance use; however, the relationship between mesolimbic resting-state functional connectivity (RSFC) and alcohol use during development remains unclear. We examined the associations between alcohol use and VTA RSFC to subcortical structures in 796 participants (12–21 years old at baseline, 51 % female) across 9 waves of longitudinal data from the National Consortium on Alcohol and Neurodevelopment in Adolescence. Linear mixed effects models included interactions between age, sex, and alcohol use, and best fitting models were selected using log-likelihood ratio tests. Results demonstrated a positive association between alcohol use and VTA RSFC to the nucleus accumbens. Age was associated with VTA RSFC to the amygdala and hippocampus, and an age-by-alcohol use interaction on VTA-globus pallidus connectivity was driven by a positive association between alcohol and VTA-globus pallidus RSFC in adolescence, but not adulthood. On average, male participants exhibited greater VTA RSFC to the amygdala, nucleus accumbens, caudate, hippocampus, globus pallidus, and thalamus. Differences in VTA RSFC related to age, sex, and alcohol, may inform our understanding of neurobiological risk and resilience for alcohol use and other psychiatric disorders